Hemophilic Arthropathy—Pathophysiology and Advances in Treatment - Katarina Kovač; Ivan Ljudevit Caktaš; Nataša Kalebota; Porin Perić (Rheumato)
Hemophilia is an X-linked genetic disorder that predominantly affects males, with females typically serving as asymptomatic carriers. Hemophilia A results from a deficiency or dysfunction of coagulation factor VIII, while a deficiency in factor IX causes hemophilia B. A less common condition, factor XI deficiency (formerly hemophilia C), is categorized as a rare bleeding disorder. The severity of hemophilia is classified based on the activity concentration of factors VIII and IX: severe (<1 IU/dL), moderate (1–5 IU/dL), and mild (6–<40 IU/dL). One of the most prevalent complications of hemophilia is hemarthrosis, bleeding into joint cavities, which, if unrecognized or untreated, can lead to hemophilic arthropathy. The pathophysiology of hemophilic arthropathy involves two key mechanisms: the accumulation of iron from blood in synovial joints, which cannot be cleared due to repeated bleeding, and the inflammatory response, resulting in synovial hyperplasia and the progressive destruction of cartilage and bone. Hemophilic arthropathy significantly impairs quality of life, causing chronic pain, joint deformities, and sometimes requiring surgical intervention. This thesis will examine the pathophysiology and management strategies for hemophilic arthropathy.